New climatic approaches to the analysis of the middle Paleolithic sequences: Combined taxonomic and isotopic charcoal analyses on a Neanderthal settlement, Les Canalettes (Aveyron, France). (20th August 2021) - Audiard, Benjamin; Meignen, Liliane; Blasco, Thierry; Battipaglia, Giovanna; Théry-Parisot, Isabelle
Abstract: Over the last decade, several studies have indicated the potential for the δ 13 C isotope signal of charcoals to act as a new local paleoclimatic/paleoenvironmental proxy, complementary to taxonomic analyses. These studies mainly focused on archeological charcoal from the Holocene series, but the potential of the method to be applied Pleistocene sequences is still under debate. Understanding climate-driven variability in stable carbon isotope ratios of modern samples is fundamental for the accurate characterization of past climate information based on the δ 13 C of charred material. In a previous study, we laid the methodological foundation to apply the method to Pleistocene contexts. Here, we present the δ 13 C isotopic signal from Pinus spp. charcoal in a well stratified middle Paleolithic site: "Les Canalettes" (Aveyron, France). We demonstrate that the use of isotopic analyses on ancient charcoal of the genus Pinus from the quaternary period could provide a reliable paleoclimatic marker with high resolution and provide data that is complementary to taxonomic studies. A continuous increase in humidity is observed, with a warming episode identified at the top of the sequence. These results place the occupation of the site in a less rigorous phase at the beginning of MIS 4 and underline the importance of the Causses in the mobility system of several generations of Neanderthals. Highlights: δ 13 C variability from individual analysis of Pleistocene charcoal is similar to that of current references frames. δ 13 C from charcoal record environmental and climatic changes from Paleolithic. Isotopic signal and charcoal taxonomic analysis seem have complementary resolutions. Isotopic signal can record climatic envent